ChemInform Abstract: Intramolecular Pd‐Catalyzed Arylation of 1‐Amidosugars: A New Route to N‐Glycosyl Quinolin‐2‐ones. Issue 38 (September 2016) - Luong, Thi Thanh Huyen; Brion, Jean‐Daniel; Lescop, Ewen; Alami, Mouad; Messaoudi, Samir
Abstract: Coupling of acrylic acids (I) with 1‐aminosugars such as (II) provides 1‐amidosugars, which are immediately subjected to Pd‐catalyzed intramolecular cyclization to form N‐glycosyl quinolinones.